Orfebrería y liturgía en San Isidoro de León. Custodias y relicarios del siglo XVI - Herráez Ortega, María Victoria (Estudios humanísticos. Geografía, historia y arte, 1997)
The treasury of San Isidoro of León keeps three magnificent mostrances of the l6th century. Two of them, corresponding to the Early Renaissance, are used as reliquaires of Saint Martino and Saint John Baptist. The change in the function doesn’t pose any structural problem; it was taking place as the monastery, which enjoyed a cultural and economic development during the l6th century, owned a more luxurious and adecuate piece for the exposition of the Sacrament. The iconographic program shows, anyway, the original function.